RETROSPECTIVE LITERATURE ON THE IMPLICATIONS OF BRUXISM FROM AN ORTHODONTIC PERSPECTIVE - Ionela Teodora Dascălu; Oana Alecu; Ștefan-Andrei Isăroiu; Stelian-; Ruxandra Voinea Georgescu; Mihaela Răescu; Oana Elena Amza; Oana Andreea Diaconu; Lelia Gheorghiță; Mihaela Jana Țuculină (Romanian Dental Association for Education, 2020)
This study is a literature review in order to obtaina synthetic and topical perspective on the implications of bruxism from an orthodontic point of view. In order to conduct this study, 52 articles and books were studied and included in the bibliographic references. Bruxism is a current oral health problem, with influences on the proper functioning of the whole body, requiring an early diagnosis and a complex, multidisciplinary management: psychological, pharmacological, physical and surgical. In this context, the orthodontist must be aware of the multiple aspects of this problem, including the possible psychological implications of orthodontic appliances or the treatment results, as obtaining an ideal occlusion does not prevent or treat bruxism.